IPOs trends and their impact on the level of venture capital divestments: Trendy IPO oraz ich wpływ na poziomie dezinwestycji funduszy venture capital - Zasępa, Piotr (Management and Administration Journal, 2021)
This paper examines the nature of venture capital activity on IPO markets. It determines that between the main IPO markets we see differences in IPO trends and venture capital activity. The period between 2000-2012 shows how divestments of venture capital change accordingly to capital market behaviour. Changing shares of venture capital stakes in IPO transactions are quite important for their functioning. This paper shows the changes in the field of IPO transactions conducted on the US, UE and Polish markets.